Penerapan Model Pembelajaran Time Token Dalam Meningkatkan Hasil Belajar Bahasa Indonesia Siswa SDN 200 Lompu Kecamatan Cina Kabupaten Bone - Sidrah Afriani Rahman; Makmur Nurdin; Hanna Lestari (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
The purpose of this study is to describe the learning model Time Token in improving the Results of Learning Indonesian Grade V student of SDN No 200 Lompu District of China Bone District. The approach in this research is qualitative approach which is descriptive. This type of research is classroom action research (PTK) which is recycled / cycle, ie various planning, implementation, observation, and reflection. The focus in this research is the Time Token learning model and the learning result of Bahasa Indonesia. Subjects in this study are students of class V SDN No. 200 Lompu District of China Bone District that requires 23 people. Data analysis technique in this research is done by reducing data, presenting data, withdrawal. Data completion technique in this research is done through observation, test, and documentation. Data analysis of qualitative data with data reduction, exposure data, and withdrawal. The results showed that the students' learning outcomes have increased at the level of cycles that have increased student learning completeness from the level of less in the first cycle and then increased in the second cycle to good category. Based on the result of the research, it can be concluded to improve the learning result of Indonesian students of class V through Time Token learning model.